Drawn to Berlin comic workshops in refugee shelters and other stories from a new Europe - Fitzgerald, Ali (Fantagraphics Books, 2018)
All Fitzgerald's students are among the record-breaking number of people who are seeking asylum in a worldwide crisis on a scale not seen since WWII, fleeing from countries such as Syria and Afghanistan. They draw images of experienced violence and careful optimism: rafts and tanks, flowers and the Eiffel Tower. In her decade in Germany, Fitzgerald experiences the highs of the creatively hopeful, along with the deep depression of the disillusioned, all while waiting to stumble onto her own glory like the great Modernists before her